Smartphone addiction is increasing across the world: A meta-analysis of 24 countries - Olson, Jay A.; Sandra, Dasha A.; Colucci, Élissa S.; Al Bikaii, Alain; Chmoulevitch, Denis; Nahas, Johnny; Raz, Amir; Veissière, Samuel P.L. (Computers in human behavior, 2022)
Smartphone ownership and screen time are increasing across the world, but there have been few attempts to quantify smartphone addiction on a global scale. We conducted a meta-analysis of studies published between 2014 and 2020 that used the Smartphone Addiction Scale, the most common measure of problematic smartphone use. We focused on adolescents and young adults (aged 15 to 35) since they tend to have the highest screen time and smartphone ownership rates. Across 24 countries, 83 samples, and 33,831 participants, we demonstrate that problematic smartphone use is increasing across the world. China, Saudi Arabia, and Malaysia had the highest scores while Germany and France had the lowest. We suggest that the clinical interpretation of these scores should be updated given current global trends. •We conducted a meta-analysis of problematic smartphone use, focusing on young adults.•The analysis (2014–2020) included 24 countries, 83 samples, and 33,831 participants.•The results showed that problematic smartphone use is increasing across the world.•China and Saudi Arabia had the highest rates while Germany and France had the lowest.•Updating the clinical interpretation of these scores may be needed in some countries.